Outpatient versus inpatient treatment for acute pulmonary embolism - Yoo, Hugo HB [UNESP]; Nunes-Nogueira, Vania Santos [UNESP]; Boas, Paulo J. Fortes Villas [UNESP]; Broderick, Cathryn (Wiley, 2022)
Background: Pulmonary embolism (PE) is a common life-threatening cardiovascular condition, with an incidence of 23 to 69 new cases per 100,000 people each year. For selected low-risk patients with acute PE, outpatient treatment might provide several advantages over traditional inpatient treatment, such as reduction of hospitalisations, substantial cost savings, and improvements in health-related quality of life. This is an update of an earlier Cochrane Review. Objectives: To assess the effects of outpatient versus inpatient treatment in low-risk patients with acute PE. Search methods: We used standard, extensive Cochrane search methods. The latest search date was 31 May 2021. Selection criteria: We included randomised controlled trials (RCTs) of outpatient versus inpatient treatment of adults (aged 18 years and over) diagnosed with low-risk acute PE. Data collection and analysis: We used standard Cochrane methods. Our primary outcomes were short- and long-term all-cause mortality. Secondary outcomes were bleeding, adverse effects, recurrence of PE, and patient satisfaction. We used GRADE to assess certainty of evidence for each outcome. Main results: We did not identify any new studies for this update. We included a total of two RCTs involving 453 participants. Both trials discharged participants randomised to the outpatient group within 36 hours of initial triage, and both followed participants for 90 days. One study compared the same treatment regimens in both outpatient and inpatient groups, and the other study used different treatment regimens. There was no clear difference in treatment effect for the outcomes of mortality at 30 days (risk ratio (RR) 0.33, 95% confidence interval (CI) 0.01 to 7.98; 2 studies, 453 participants; low-certainty evidence), mortality at 90 days (RR 0.98, 95% CI 0.06 to 15.58; 2 studies, 451 participants; low-certainty evidence), major bleeding at 14 days (RR 4.91, 95% CI 0.24 to 101.57; 2 studies, 445 participants; low-certainty evidence) and at 90 days (RR 6.88, 95% CI 0.36 to 132.14; 2 studies, 445 participants; low-certainty evidence), minor bleeding (RR 1.08, 95% CI 0.07 to 16.79; 1 study, 106 participants; low-certainty evidence), recurrent PE within 90 days (RR 2.95, 95% CI 0.12 to 71.85; 2 studies, 445 participants; low-certainty evidence), and patient satisfaction (RR 0.97, 95% CI 0.90 to 1.04; 2 studies, 444 participants; moderate-certainty evidence). We downgraded the certainty of the evidence because the CIs were wide and included treatment effects in both directions, the sample sizes and numbers of events were small, and it was not possible to determine the effect of missing data or the presence of publication bias. The included studies did not assess PE-related mortality or adverse effects, such as haemodynamic instability, or adherence to treatment. Authors' conclusions: Currently, only low-certainty evidence is available from two published randomised controlled trials on outpatient versus inpatient treatment in low-risk patients with acute PE. The studies did not provide evidence of any clear difference between the interventions in overall mortality, bleeding, or recurrence of PE.